2015
DOI: 10.1016/j.bjan.2013.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da associação ropivacaina‐pancurônio na transmissão neuromuscular e eficácia da neostigmine e 4‐aminopiridina na reversão do bloqueio: estudo experimental

Abstract: Ropivacaine increased the neuromuscular block produced by pancuronium. The complete antagonism with 4-aminopyridine suggests presynaptic action of ropivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Similarly to other studies,[ 3 ] we observed that a 50% enantiomeric excess bupivacaine mixture in the concentration used did not alter MPs of muscle fibres. Muscle MP was maintained within normal limits.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similarly to other studies,[ 3 ] we observed that a 50% enantiomeric excess bupivacaine mixture in the concentration used did not alter MPs of muscle fibres. Muscle MP was maintained within normal limits.…”
Section: Discussionsupporting
confidence: 90%
“…The influence of local anaesthetics on these parameters may indicate a presynaptic action, consequently decreasing acetylcholine release or reducing the sensitivity of the postjunctional membrane to acetylcholine. [ 1 3 9 10 11 12 13 ] In our study, impaired neurotransmitter release was observed. This event was demonstrated by a progressive decrease in the frequency and amplitude of MEPPs.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations